Tax Policy and CO2 Emissions – An Econometric Analysis of the German Automobile Market - Colin Vance; Markus Mehlin (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
In addition to efficiency standards and consumer information, car-related taxes constitute one of three pillars of the European Commissions strategy to reduce CO2 emissions from passenger cars. A longstanding question concerns the effectiveness of such taxes in determining the car-purchasing behavior of households. Several recent studies suggest that purchases are primarily determined by retail costs rather than by taxes, the latter of which are typically incurred over the lifetime of the car. Using panel data on new-car registrations in Germany, Europe's largest car market, the present paper addresses this issue with an econometric analysis of the impact of fuel costs and circulation taxes on car market shares. By employing a nested logit model that explicitly recognizes the segmented structure of the car market, the analysis takes account of correlation in unobserved shocks among cars belonging to the same market segment. Moreover, given the panel structure of the data, a fixed effects estimator is employed to control for the influence of unobservable, time- invariant automobile attributes that could otherwise induce biases in the estimated coefficients. Contrasting with much of the evidence garnered to date, the results suggest that circulation taxes and fuel costs significantly determine car market shares, and hence may serve as effective instruments in influencing the composition of the car fleet and associated CO2 emissions.
Keywords: C51; L91; Q48; 330; Fuel tax; circulation tax; car market; Germany; panel data; nested logit model; Kraftfahrzeugmarkt; Nachfrage; Kraftfahrzeugsteuer; Mineralölsteuer; Ökosteuer; Verkehrsökologie; Kohlendioxid; Schätzung; Deutschland